Form factors of local operators in supersymmetric quantum integrable models. (20th April 2017) - Fuksa, J; Slavnov, N A
Abstract: We apply the nested algebraic Bethe ansatz to the models with g l ( 2 | 1 ) and g l ( 1 | 2 ) supersymmetry. We show that form factors of local operators in these models can be expressed in terms of the universal form factors. Our derivation is based on the use of the RTT -algebra only. It does not refer to any specific representation of this algebra. We obtain thus determinant representations for form factors of local operators in the cases where an explicit solution of the quantum inverse scattering problem is not known.